Quantitation of Antibody to Non-Hemagglutinating Viruses by Single Radial Hemolysis: Serological Test for Human Coronaviruses - Hierholzer, John C. (1977)
A single radial hemolysis test was developed for quantitation of specific antibody to non-hemagglutinating viruses. With the human coronaviruses as models, this test utilizes the binding properties of the chromic cation to attach viruses to glutaraldehyde-treated sheep erythrocytes. The most satisfactory system consisted of stabilizing washed sheep erythrocytes with 0.0073% glutaraldehyde for 15 min at 23°C, binding a high concentration of virus to a 25% erythrocyte suspension with 0.0016% chromic chloride for 20 min at 23°C, stopping the reaction with phosphate-saline, and finally mixing the treated, rewashed cells with complement and agarose at 45°C to prepare a slide gel. The gel mix, which was dispensed in plastic plates (23 by 73 mm) in 3-ml volumes, consisted of 1% agarose, 0.1% sodium azide, 5% reconstituted complement, and 0.82% treated cells. Wells 2 mm in diameter were loaded with 5 μl of antiserum, incubated for 18 h at 4°C for diffusion of antiserum and fixation of complement, and then incubated for 8 to 24 h at 37°C for development of hemolysis zones. The diameter of a zone was linearly related to antibody concentration, as determined by conventional serological tests. This single radial hemolysis test was applicable to human and animal coronaviruses and to selected serotypes of the adenovirus, picornavirus, rhabdovirus, and rotavirus groups.